Pelatihan dan Pendampingan Pembuatan Pupuk Organik dan Pestisida Nabati pada Perkumpulan Tani Pemuda - Utami, Desy Cahyaning; Swasono, Muh. Aniar Hari; Ainiyah, Roisatul (Universitas Muhammadiyah Malang, 2025)
Purpose – This training and mentoring activity aims to provide solutions to problems by introducing techniques for making organic fertilizers and vegetable pesticides that are easy to apply. This training not only focuses on theory, but also on direct practice in the field, so that participants can feel the real benefits of this training. Design/methodology/approach – The method used in this training and mentoring starts from several stages consisting of the preparation stage including, identification of needs, use of tools and materials, and selection of locations. The second is the training implementation stage, which includes the provision of materials and demonstrations or direct practice with participants. Findings – After the training and mentoring at Perkumpulan Tani Pemuda Darul Mukmin, some significant results were obtained, both in terms of knowledge and skills. For the improvement of participants' knowledge before the training, most of them were still dependent on chemical fertilizers and synthetic pesticides due to limited knowledge of organic farming methods. Through this activity, their understanding of the importance of organic fertilizers and plant-based pesticides increased. While in terms of skills, participants can make organic fertilizers and vegetable pesticides from materials in the surrounding environment. Originality/value – Trainees are able to make and are ready to apply it on their own land.